The Role of the Catholic Church in Curbing Youth Unemployment, Insecurity, and Radicalisation in Kenya (National Security: A Journal of the National Defence University-Kenya, 2025)
Youth unemployment, insecurity, and radicalisation remain pressing and intertwined challenges in Kenya, with a disproportionate impact on urban and peri-urban youth. While government responses have been documented extensively, the role of faith-based organisations (FBOs) as non-state actors in youth empowerment and security promotion remains underexplored in academic discourse. This study fills this critical gap by analysing the strategic contributions of the Catholic Church in Kenya in mitigating youth unemployment, curbing radicalisation, and promoting community security. Drawing on a qualitative research design, the study utilised 25 semi-structured interviews with Catholic clergy, youth beneficiaries, and program officers, as well as content analysis of over 40 institutional reports and public documents from diocesan development offices across Nairobi, Kisumu, and Eldoret. Findings indicate that Catholic-led initiatives have directly supported over 20,000 youth through vocational training, entrepreneurship incubation, peacebuilding workshops, and counselling services between 2015 and 2023. Programs such as the Catholic Justice and Peace Commission’s youth empowerment centres and Caritas Kenya’s economic resilience hubs have enhanced skills acquisition, social cohesion, and nonviolent conflict resolution. The Church has also contributed to national policy conversations by advocating for youth-focused development strategies and forging interfaith alliances for peace. This paper recommends the urgent expansion of Catholic digital training academies, increased resource allocation to faith-based organisation (FBO)-led vocational institutions, and formalised partnerships between the Church, state, and private sector. By anchoring its interventions in moral teachings and providing practical livelihood support, the Catholic Church exemplifies how FBOs can be transformative agents in Kenya’s security and development architecture.
Keywords: Catholic Church, Youth Unemployment, Radicalisation, Economic Empowerment, and Peacebuilding